FOLKLORE AND FAIRY-TALE ARCHETYPES AS A POETIC MECHANISM OF MORAL MEANING IN THE NOVELS OF CHARLES DICKENS (Symposium on Natural and Applied Sciences, 2026)
This article investigates the function of folklore and fairy-tale archetypes in the poetics of Charles Dickens, arguing that they operate not as decorative borrowings but as a systematic mechanism for the expression of moral value. While the presence of fairy-tale motifs in Dickens has long been noted, scholarship has tended to register their similarity to folk material rather than to analyse their structural moral function. Taking Oliver Twist (1837–1839) and Great Expectations (1860–1861) as principal cases, and drawing on the wider corpus, the study shows how the fairy-tale opposition of good and evil, the motif of magical transformation, and the figure of the secret benefactor are reworked by Dickens into instruments of ethical analysis. The investigation employs close reading and a comparative-typological method. The findings indicate that the archetypal substratum performs three interrelated tasks: it organizes the moral architecture of the plot, it grounds the reader’s confidence in the ultimate meaningfulness of moral choice, and it allows the writer to combine realistic social critique with the affirmation of enduring moral values. The study contributes to an understanding of Dickensian poetics in which folklore is a constitutive rather than an ornamental element.
Keywords: Charles Dickens, folklore, fairy-tale archetype, moral ideal, magical transformation, secret benefactor, Oliver Twist, Great Expectations, poetics, Victorian novel.